TREATMENT OF NSAID-INDUCED GASTROPATHY WITH REBAGIT (World Bulletin of Public Health, 2024)
More than 30 million people in the world take NSAIDs daily, and in 2/3 of cases - without a doctor’s prescription or supervision. One of the most common negative manifestations associated with the use of this group of drugs is gastropathy induced by taking NSAIDs (NSAID gastropathy), which is characterized by the occurrence of erosions and ulcers of the mucous membrane (MU) of the stomach and duodenum. Of the reviewers, 8/11% are men and 65/89% are women. Women are 8 times more susceptible to the development of NSAID-induced gastropathy than men (Table 1). The average age of men was 57 years, and for women 46 years. The quality of life in patients in the control group, before the start of treatment (standard treatment - without rebaits), the coefficient was equal to 32.4. After completing a 6-week course of treatment, this figure decreased to 31.8. When analyzing the study data, it was revealed that patients suffering from rheumatoid arthritis and complications of NSAID-induced gastropathy, the risk of blood loss was on average 2.9%. Particularly important is the attachment of patients to the course of treatment for gastrointestinal diseases, in particular NSAID-induced gastropathy, which contributed to effective treatment, which is reflected in the MARS questionnaire.
Keywords: NSAID-induced gastropathy; drug Rebagit; EQ-5D and MARS; Charlson score